2014
DOI: 10.1142/s1793604714500428
|View full text |Cite
|
Sign up to set email alerts
|

On the functional degradation of binary titanium–tantalum high-temperature shape memory alloys — A new concept for fatigue life extension

Abstract: High-temperature shape memory alloys are promising candidates for actuator applications at elevated temperatures. Ternary nickeltitanium-based alloys either contain noble metals which are very expensive, or suffer from poor workability. Titanium-tantalum shape memory alloys represent a promising alternative if one can avoid the cyclic degradation due to the formation of the omega phase. The current study investigates the functional fatigue behavior of Ti-Ta and introduces a new concept providing for pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
21
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
1
21
1
Order By: Relevance
“…[8][9][10][11] Ti-27Ta-5Al was shown to be stable for up to 20 thermal cycles, where the maximum test temperature was about 250 ○ C. 10 Experiments conducted on Ti-30Ta and Ti-30Ta-3Al in related studies revealed that changes in test procedure like employing a higher number of cycles at higher temperatures or long-term creep testing can lead to severe functional degradation. 12,13,19 In case of cyclic thermo-mechanical loading, the rate of degradation was strongly reduced by Al additions, but qualitatively a similar degradation behavior was found. 13 In addition, it was shown that transformation strain capability can be restored by short-time annealing treatments.…”
supporting
confidence: 56%
See 4 more Smart Citations
“…[8][9][10][11] Ti-27Ta-5Al was shown to be stable for up to 20 thermal cycles, where the maximum test temperature was about 250 ○ C. 10 Experiments conducted on Ti-30Ta and Ti-30Ta-3Al in related studies revealed that changes in test procedure like employing a higher number of cycles at higher temperatures or long-term creep testing can lead to severe functional degradation. 12,13,19 In case of cyclic thermo-mechanical loading, the rate of degradation was strongly reduced by Al additions, but qualitatively a similar degradation behavior was found. 13 In addition, it was shown that transformation strain capability can be restored by short-time annealing treatments.…”
supporting
confidence: 56%
“…2 depicts the evolution of A s , A f and M s as well as the evolution of transformation strain as a function of cycle number. In previous work a strong decrease in transformation temperatures occurred after each cycle, 12,13 which was triggered by the nucleation and growth of !-phase particles. In contrast, the transformation temperatures for the current Ti-30Ta-3Al sample increase up to the 100th cycle.…”
mentioning
confidence: 86%
See 3 more Smart Citations